Assessing the Impact of Sea Level Rise and Resilience Potential in the Caribbean : 360° Resilience Background Paper - Giardino, Alessio; Leijnse, Tim; Torres Duenas, Luisa; Athanasiou, Panos; Haasnoot, Marjolijn (World Bank, Washington, DC, 2021)
The Caribbean region suffers major economic losses from natural hazards such as flooding due to storms, cyclones, extreme waves, winds and precipitation, coastal erosion, volcanic eruptions and landslides. Consequently, as typical at most small coastal states, when a disaster strikes, a large part of the population, infrastructure and businesses, generally concentrated in the coastal areas, are directly or indirectly affected. Climate change and sea level rise (SLR), in combination with socio-economic growth, are likely to exacerbate this situation, which is already critical for many of these countries. In particular, the effect of SLR will lead to more frequent and intense flooding events and chronical coastal erosion, with a direct effect on the local and regional economies. In this study, a regional estimation of the effects of SLR in terms of coastal flooding and erosion of sandy beaches was carried out for 18 countries in the Caribbean with the aim of deriving proxies to evaluate the resilient potential of each country and their potential to adaptation. The (change in) risk resulting from SLR was estimated until 2100 under different SLR scenarios and socio-economic pathways.